Risk of Guillain–Barré syndrome following pandemic influenza A(H1N1) 2009 vaccination in Germany1. (10th May 2014) - Prestel, Jürgen; Volkers, Peter; Mentzer, Dirk; Lehmann, Helmar C.; Hartung, Hans‐Peter; Keller‐Stanislawski, Brigitte; for the GBS Study Group
ABSTRACT Purpose A prospective, epidemiologic study was conducted to assess whether the 2009 pandemic influenza A(H1N1) vaccination in Germany almost exclusively using an AS03‐adjuvanted vaccine (Pandemrix) impacts the risk of Guillain–Barré syndrome (GBS) and its variant Fisher syndrome (FS). Methods Potential cases of GBS/FS were reported by 351 participating hospitals throughout Germany. The self‐controlled case series methodology was applied to all GBS/FS cases fulfilling the Brighton Collaboration (BC) case definition (levels 1–3 of diagnostic certainty) with symptom onset between 1 November 2009 and 30 September 2010 reported until end of December 2010. Results Out of 676 GBS/FS reports, in 30 cases, GBS/FS (BC levels 1–3) occurred within 150 days following influenza A(H1N1) vaccination. The relative incidence of GBS/FS within the primary risk period (days 5–42 post‐vaccination) compared with the control period (days 43–150 post‐vaccination) was 4.65 (95%CI [2.17, 9.98]). Similar results were found when stratifying for infections within 3 weeks prior to onset of GBS/FS and when excluding cases with additional seasonal influenza vaccination. The overall result of temporally adjusted analyses supported the primary finding of an increased relative incidence of GBS/FS following influenza A(H1N1) vaccination. Conclusions The results indicate an increased risk of GBS/FS in temporal association with pandemic influenza A(H1N1) vaccination in Germany. © 2014 The Authors. Pharmacoepidemiology and Drug Safety published by John Wiley & Sons, Ltd.